Analisis Verzet Terhadap Putusan Verstek dalam Hukum Acara Perdata - Fauziah Lubis; Tazkiya Asri Syam; Liza Fauzanti Sagala; Anggina Elsa Ritonga; Lusi Febriani; Sigit Sigit (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the legal remedies for denial of default in the civil procedural law system in Indonesia. The main problem raised is how the denial mechanism can provide legal protection for defendants who are not present at the trial, and how the application of denial in judicial practice is related to the principle of fair and speedy trials. The background of this study is based on the phenomenon of many civil cases being decided by default due to the absence of the defendant, which then leads to the submission of denial as a means of protecting the defendant's rights. The research method used is normative juridical with a statutory approach and case studies. Data were obtained through a literature study of laws and regulations, court decisions, and relevant literature, and analyzed qualitatively. The results of the study indicate that denial is an important legal right for defendants to defend themselves against unilaterally imposed decisions. However, in practice, the implementation of denial is often hampered by administrative factors, the defendant's ignorance of their rights, and different interpretations by law enforcement officers regarding the deadline for submitting denial. Therefore, it is necessary to strengthen regulations and socialize the mechanism of verzet so that the principle of justice in the civil trial process can be realized optimally.